In-the-Field Authentication of Grapevine (Vitis vinifera L.) cv: Albariño Using Chlorotype Discrimination and a Single SNP Interrogation by LAMP - Javier Quinteiro; Lara Quinteiro; Angela Díaz-Fernández; Manuel Rey-Méndez; Javier Ibáñez; Emilia Díaz-Losada (Australian Journal of Grape and Wine Research)
Authentication of grapevine cultivars, Vitis vinifera L., is difficult, especially when analytical specimens lack diagnostic ampelographic characters, which prevents the verification of traceability systems aimed at guaranteeing varietal integrity. This issue is problematic when viticultural strategies and regulations associated with high-value wine-producing geographical areas rely on extensive control and monitoring of valuable cultivars. Varietal identification based on grapevine molecular markers is a standardized methodology that requires a specialised laboratory for its application. In contrast, the use of loop-mediated isothermal amplification (LAMP) allows DNA markers to be characterized quickly and easily, without the need for skilled personnel, allowing implementation in-situ or in-the-field. Simultaneous identification of the chlorotype and the interrogation of a single SNP using a portable device have allowed the first discrimination in-the-field of grafted grapevines, without appreciable ampelographic characters, as belonging to the valuable “Albariño” cultivar. This methodology constitutes a valuable tool for cultivar discrimination and can be efficiently implemented in the traceability of valuable grapevine genetic resources.